Beyond the Sinister and the Fantastic: Concept of the Telluric and Its Aplication in an Analysis of "Hamlet" - Espinosa, Antonio César Morón (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This article hopes to establish a new concept in literary theory in order to be used as a tool for the analysis of texts: telluric. Its specific research is carried out in two steps: first it has been framed within a theoretical universe with which keeps certain relationship. In a second movement, it confronts and emphasizes its contrasts with the fundamental concepts of that theoretical universe: the Freudian uncanny, «unheimlich», and the fantastic, «fantastique», from Todorov. Finally, in order to check its hermeneutic possibilities, the concept of telluric has been applied to the analysis of Hamlet.